Struktur Tata Kelola Hijau dan Kendala Pendanaan Perusahaan di Era Teknologi Digital: Peran Tingkat Keseimbangan Ekuitas sebagai Variabel Moderasi - Fauzi Fauzi; Dwi Hajriani Denta; Putri Ramadhanti; Shabila Fitri Aulia (ARZUSIN, 2025)
Companies in the digital technology era face substantial challenges in obtaining funding, partly due to increasing demands for the implementation of sustainability practices. Problems arise when green governance structures designed to support sustainability instead have the potential to exacerbate financing constraints. This study aims to analyze the effect of green governance structure on corporate financing constraints and to assess the role of the equity balance level as a moderating variable. The research uses data from manufacturing firms listed on the Indonesia Stock Exchange, selected through purposive sampling, resulting in 17 companies and a total of 68 observations. Data were analyzed using panel regression with E-Views software. The findings show that green governance structure has a positive and significant effect on corporate financing constraints in the digital technology era. However, when moderated by the equity balance level, green governance structure has a negative and significant effect on financing constraints, indicating that equity can weaken the impact of green governance on funding difficulties. The study concludes that green governance can intensify funding pressure, but equity balance functions as a buffer that strengthens the firm’s funding capacity. The implications encourage management to reinforce equity structures in order to sustain the implementation of green governance without increasing the burden of financing constraints.